Fast wideband scattering analysis of large-scale finite-sized periodic arrays with planar cells using ASED basis function and interpolation technique. Issue 13 (2nd September 2019) - Fu, Wei Jie; Du, Ping; Hu, Rong Chuang
ABSTRACT: In this paper, the accurate sub-entire-domain (ASED) basis function method is combined with the interpolation technique to efficiently analyze the wideband electromagnetic scattering from the large-scale finite-sized periodic arrays with planar cells. Comparing with the conventional method of moments (MoM), the ASED basis function method can tremendously reduce the number of unknowns. Thus, the computational complexity can be tremendously reduced. It is a single-frequency technique. The impedance matrix needs to be calculated repeatedly at each frequency. The interpolation technique can speed up the wideband simulation because the impedance matrices can be efficiently obtained using the interpolation technique. To validate the accuracy and efficiency of the proposed method, several numerical examples are carried out. Simulation results show that the results of the proposed technique agree well with those of the ASED bases. Both the CPU time and the memory cost are significantly reduced by using the proposed method.